Different suplementation strategies with carbohydrate and subsequent glicemic answer during indoor activity - Baganha, Ronaldo Julio; Santos, Gabriel Ferreira Souza e; Moreira, Rafael Augusto Coutinho; Tiburzio, Alessandro Silva; Macedo, Renata de (Journal of Physical Education (Maringá), 2008)
During sports practice the metabolism increases in a way to provide for any metabolic demand imposed by the increase in the muscular metabolism. The use of muscular glycogen and blood glucose increase, and a fall in the glycogen as in the glycemic concentration can retract fatigue. Studies have been showing that supplement with carbohydrate delays fatigue, preserves the stocks of glycogen and supplies extra energy to the tissues in activity. The objective of the present study was to analyze the effects of carbohydrate supplement on the glycemic blood of professional cyclists during the practice of indoor cycling. The athletes pedaled in a stationary bicycle for 120 minutes, minimal intensity at 60 % and the maximum at 75 % of the utmost cardiac frequency. The results suggest that carbohydrate supplement does not affect in a significant form the glycemic concentration of those athletes during 120 minutes of indoor activity.